2022
DOI: 10.3390/life12030389
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 as a Potential Biomarker for Risk Assessment of Pulmonary Hypertension in Patients Undergoing TAVR?

Abstract: Background: Severe aortic valve stenosis (AS) is associated with pulmonary hypertension (PH) and has been shown to limit patient survival. Soluble suppression of tumorigenicity-2 (sST2) is a cardiovascular biomarker that has proven to be an important prognostic marker for survival in patients undergoing transcatheter aortic valve replacement (TAVR). The aim of this study was to assess the importance of the sST2 biomarker for risk stratification in patients with severe AS in presence or absence of PH. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The selection of biomarkers was based on extensive literature research as well as preliminary work of our own research group: sST2 has already been described as a potentially valuable biomarker for risk stratification of PH in TAVR patients [ 17 ]. IGF-BP2 is considered a general risk predictor in patients with severe AS and TAVR [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selection of biomarkers was based on extensive literature research as well as preliminary work of our own research group: sST2 has already been described as a potentially valuable biomarker for risk stratification of PH in TAVR patients [ 17 ]. IGF-BP2 is considered a general risk predictor in patients with severe AS and TAVR [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it could be shown in multivariate binary logistic regression that sST2 was a relevant independent predictor for the detection of potential PH. This has already been confirmed recently by our own working group using a collective of patients with severe AS and available right heart catheterization data, on the basis of which PH was verified by the absolute gold standard [20]. It may well be hypothesized that removal of the aortic valve stenosis decreases the corresponding left ventricular mechanical stress; however, the already fixed pulmonary hypertension leads to continued secretion of sST2 from cardiomyocytes during sustained right ventricular stress.…”
Section: Sst2mentioning
confidence: 60%
“…Reportedly, the sST2 level was significantly elevated in patients with severe aortic valve stenosis who presented with pulmonary hypertension and associated with earlier death and high mortality ( 29 ). Another study demonstrated the prognostic value of sST2, which is an independent predictor of adverse outcomes in different aortic diseases ( 30 ).…”
Section: Discussionmentioning
confidence: 99%